KONTRIBUSI MOTIVASI BELAJAR TERHADAPA HASIL BELAJAR MATA PELAJARAN GAMBAR BANGUNAN SISWA SMK NEGERI 2 SOLOK - 43-51 . Ice Syafsensi (CIVED, 2013)
The background of this research was the low achievement of second grade students at first semester test in academic year 2011/2012, 37,03% TGB1 students and 80,77% of TGB2 students got under standard grade for Gambar Bangunan subject. This research was a correlation study which was aimed to explain the contribution of learning motivation on the student achievement of Gambar Bangunan subject at SMK Negeri 2 Solok. The population of this study was all of TGB students of second grade whish are 43 students. The sample was taken by using total sampling. The research data was taken by using Likert scale questionnaire, the variable (X) was the learning motivation, and the variable (Y) was the student achievement. The analysis of data was done through three steps : (1) Data description, (2) Pre-Analysis testing, (3) and Hypothesis testing. Based on the data analysis, it was assumed that correlative coefficient was (r=0,447)on the probability 0,003 < than Alpha significant 0,05. The result on students motivation was 77,21%. The hypothesis of this research was accepted with 19,9% of the contribution of student learning motivation on student achievement Gambar Bangunan subject at SMK Negeri Solok. Key words :        motivasi belajar, hasil belajar, mata pelajaran gambar bangunan